2014
DOI: 10.1002/aic.14415
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Monte Carlo simulations of the adsorption of chiral alcohols in a homochiral metal‐organic framework

Abstract: Grand canonical Monte Carlo (GCMC) simulations with configurational biasing were used to study the enantioselective adsorption of four alkanols in a homochiral metal‐organic framework, known as hybrid organic‐inorganic zeolite analogue HOIZA‐1. Conventional GCMC simulations are not able to converge satisfactorily for this system due to the tight fit of the chiral alcohols in the narrow pores. However, parallel tempering and parallel mole‐fraction GCMC simulations overcome this problem. The simulations show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 69 publications
0
10
0
Order By: Relevance
“…Other implemented methods in RASPA to improve the efficiency of MC simulations are parallel-tempering and mole fraction replica exchange. [46,47] …”
Section: Efficient Algorithms For Open Ensemblesmentioning
confidence: 99%
“…Other implemented methods in RASPA to improve the efficiency of MC simulations are parallel-tempering and mole fraction replica exchange. [46,47] …”
Section: Efficient Algorithms For Open Ensemblesmentioning
confidence: 99%
“…The result consists with our explanation with the bonding between the open metal site and the alcohol. For further investigation, molecular simulations would be helpful. , …”
Section: Resultsmentioning
confidence: 99%
“…For further investigation, molecular simulations would be helpful. 55,56 The results showed that the appropriate pore size of the adsorbent was essential for adsorption at low pressure. In general, for material development of porous coordination polymers including metal organic frameworks, the surface area had to expand as much as possible to increase the capacity.…”
Section: Methodsmentioning
confidence: 99%
“…But these species are not part of the original crystal, and they might have an influence on the fitted charges. Nevertheless, ESP derived charges, have been the most widely used methods to obtain atomic partial charges, with large success in modelling MOFs [44,52,76,[84][85][86][87][88][89][90][91]. Only in the last few years they have been gradually replaced by other methods better suited for studying periodic systems.…”
Section: G Electrostatic Potential (Esp) Derived Chargesmentioning
confidence: 99%